The TNF-Alpha Inducing Protein is Associated With Gastric Inflammation and Hyperplasia in a Murine Model of Helicobacter pylori Infection - Morningstar-Wright, Lindsay; Czinn, Steven J.; Piazuelo, M. Blanca; Banerjee, Aditi; Godlewska, Renata; Blanchard, Thomas G. (Frontiers in Pharmacology, 2022)
Helicobacter pylori (H. pylori) is a gram-negative bacterium that colonizes the human stomach leading to the development of chronic gastritis, peptic ulcers and gastric cancer. A combination of host, environment and bacterial virulence factors contribute to disease development. The H. pylori TNFα inducing protein (Tipɑ) is a virulence factor shown to induce multiple pro-inflammatory cytokines in addition to TNFα in vitro. The goal of the present study was to elucidate the role of Tipα in promoting inflammation in vivo and to identify the molecular pathways associated with Tipα associated virulence. Mice were infected with wild-type Sydney strain (SS1) or a tipα mutant (Δtipα) for one month and four months. We also completed a second 4 month infection including a 1:1 SS1 to Δtipα co-infected group in addition to SS1 and Δtipα infected groups. The expression of TNFα, and KC were significantly higher in the SS1 infected group compared to both uninfected control (naïve) and Δtipα groups. Mice infected with Tipα expressing SS1 induced more severe histological gastritis and developed hyperplasia compared to Δtipα infected mice. Microarray analysis of gastric epithelial cells co-cultured with recombinant Tipα (rTipα) demonstrates up-regulation of the NFκB pathway. This data suggest Tipα plays an important role in H. pylori induced inflammation.